Coagulation Parameters as a Prognostic Factor for Mortality in a Neonate with Duodenal Obstruction - Desdwianto, Dito; Setiawan, Ariandi; Hariastawa, IGB Adria; Budiman, Sarwendah Pratiwi (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Although the mortality cases of duodenal obstruction are only about 5%, this abnormality remains a burden in pediatric surgery. Several conditions can worsen a patient’s outcome and a proper understanding of the coagulation parameters is vital for a good outcome. Methods: This study was a descriptive-analytic study. Data of duodenal obstruction in neonate patients were taken from medical records from 2016 to 2020 .  The data were then processed using SPSS 26.0 Results: From 59 samples of neonates with duodenal obstruction, most of them were born aterm pregnancy 38 (64%) patients, with male 32 patients and female 27 patients. There were  neonates died based on complete obstruction 12 (20.3%), there was no significantly different neonates died between low birth weight and normal birth weight 9 (15.3%). The most commonly performed surgical procedure was kimura procedure 43 patients, with 14% patients was died. Coagulation parameters platelets, Protrombine time (PT), and Activated Partial Thromboplastin Time (APTT), only APTT there was significance correlation with P- value (0.016) , OR 3.98 Conclusion: There was a significant correlation between Activated Partial Thromboplastin Time (APTT) and mortality, with abnormal APTT had 3.98 times higher risk of dying than normal.